Reduction of total harmonic distortion of three-phase inverter using alternate switching strategy - Nur Arifah Ramli; Auzani Jidin; Zulhani Rasin; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Alternating current (AC) electrical drives mainly require smaller current (or torque) ripples and lower total harmonic distortion (THD) of voltage for excellent drive performances. Normally, in practice, to achieve these requirements, the inverter needs to be operated at high switching frequency. By operating at high switching frequency, the size of filter can be reduced. However, the inverter which oftenly employs insulated gate bipolar transistor (IGBT) for high power applications cannot be operated at high switching frequency. This is because, the IGBT switching frequency cannot be operated above 50 kHz due to its thermal restrictions. This paper proposes an alternate switching strategy to enable the use of IGBT for operating the inverter at high switching frequency to improve THD performances. In this strategy, each IGBT in a group of switches in the modified inverter circuit will operate the switching frequency at one-fourth of the inverter switching frequency. The alternate switching is implemented using simple analog and digital integrated circuits.